Analysis on The Influence Factors of Transmission Line Project Cost Based on Random Forest Model. Issue 4 (March 2021) - Ma, Li; Zhou, Ming; Lu, Shengwei; Wang, Qixin; Liao, Shuang; Ming, Yue; Wang, Sicong
Abstract: There are many factors influencing the cost of transmission line project. The complex construction environment, different construction level and other factors could lead to large differences in the cost of comparable transmission line projects under the same voltage level. Based on the division of the transmission line projects, this paper analyzes and identifies the main factors affecting the cost of transmission line project. The random forest model is used to select 15 of the influencing factors. And then, this paper verifies the main factors selected, providing references for prediction.